Fluorescence-based quantitative characterization of structural phase transitions in Li+/Er3+:BaTiO3 ferroelectric ceramics. (30th November 2021) - Li, Jiaming; Sun, Enwei; Ma, Yaping; Zheng, Huashan; Zhao, Hua; Zhang, Zhiguo
Abstract: We propose a method to quantitatively characterize the fine phase transition processes of Li + /Er 3+ :BaTiO3 (BLET) ferroelectric materials by observing fluorescence wavelength shift. A lithium and erbium co-doped barium titanate ferroelectric ceramic was fabricated and the down-conversion infrared fluorescence spectra of the transition 4 I13/2  →  4 I15/2 were measured as a function of temperature. The three structural phase transition processes, namely rhombohedral–orthorhombic, orthorhombic–tetragonal, and tetragonal–cubic transformations, determined by X-ray diffraction results are accompanied by corresponding changes in the position of the fluorescence peaks, yielding an exact consistency. This contactless, non-destructive and spatially-resolved fluorescence method provides a localized quantitative analysis for the phase transition processes of BLET ceramics. As this method is based on the fluorescence peak wavelength dependence on the crystal environment, it may potentially be used to characterize the phase transitions in other ferroelectric materials. Graphical abstract: Highlights: Three temperature induced phase transitions process of Li + /Er 3+ :BaTiO3 ceramics were successfully detected by fluorescence wavelength shift. The three structural phase transition processes determined by X-ray diffraction results, are accompanied by corresponding changes in the position of the fluorescence peaks, showing an exact consistency. This contactless, non-destructive and spatially-resolved fluorescence method provides a localized quantitative analysis for the phase transition processes of Li + /Er 3+ :BaTiO3 ceramics.